2010
DOI: 10.1111/j.1460-2466.2010.01513.x
|View full text |Cite
|
Sign up to set email alerts
|

Defining Media Enjoyment as the Satisfaction of Intrinsic Needs

Abstract: This article presents a model of enjoyment rooted in self-determination theory (Deci & Ryan, 1985) that includes the satisfaction of three needs related to psychological wellbeing: autonomy, competence, and relatedness. In an experiment designed to validate this conceptualization of enjoyment, we manipulate video game characteristics related to the satisfaction of these needs and examine their relative effects on enjoyment. The validated model explains 51% of the variance in enjoyment, even without including n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
438
6
15

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 471 publications
(487 citation statements)
references
References 33 publications
28
438
6
15
Order By: Relevance
“…This limitation clearly results from the focus EMOTIONAL GRATIFICATIONS 31 on non-interactive entertainment media such as movies and TV series. Studies on need satisfaction in the context of interactive entertainment (Reinecke et al, in press;Tamborini et al, 2010) have found that mastering the challenges presented in video games can satisfy individuals' needs for competence and autonomy, which in turn leads to greater enjoyment of the game. It is therefore important to keep in mind that interactive entertainment can satisfy intrinsic needs and promote psychological well-being in ways that are not covered by the present scales.…”
Section: Limitations and Outlookmentioning
confidence: 99%
See 4 more Smart Citations
“…This limitation clearly results from the focus EMOTIONAL GRATIFICATIONS 31 on non-interactive entertainment media such as movies and TV series. Studies on need satisfaction in the context of interactive entertainment (Reinecke et al, in press;Tamborini et al, 2010) have found that mastering the challenges presented in video games can satisfy individuals' needs for competence and autonomy, which in turn leads to greater enjoyment of the game. It is therefore important to keep in mind that interactive entertainment can satisfy intrinsic needs and promote psychological well-being in ways that are not covered by the present scales.…”
Section: Limitations and Outlookmentioning
confidence: 99%
“…The first type of entertainment gratification that is based on affect regulation is relatively well researched (for overviews, see Knobloch-Westerwick, 2006;Oliver, 2009;Vorderer, Klimmt, & Ritterfeld, 2004), whereas evidence concerning the role of emotional entertainment experiences in the gratification of social and cognitive needs has only recently begun to emerge in a consistent manner (cf., Cupchik, 2011;Oliver & Bartsch, 2010;Oliver & Raney, 2011;Reinecke, Tamborini, Grizzard, Lewis, Eden, & Bowman, in press;Tamborini et al, 2010;Vorderer & Ritterfeld, 2009). The present research aims to advance this line of inquiry by providing a systematic assessment of gratifications that can be directly or indirectly associated with the experience of emotions in media use, and by analyzing how different kinds of emotions can contribute to different types of entertainment gratification.…”
Section: Rationale Of the Present Researchmentioning
confidence: 99%
See 3 more Smart Citations